PRELIMINARY STUDY ON THE REARING OF CHILKA PRAWN("KANTALA ")PENAEUS INDUS H. MILNE -EDWARD IN THE BRACKISH WATER PONDS AT KESHPUR (ORISSA) - MOHANTY, S K (Fishery Technology, 2017)
Results of the experimental rearing of Penaeus indicus without supplemental feeding in the unfertilized brackishwater ponds in the fore-shore of the Chilka lake are presented in this paper. Higher rate of survival was recorded lin the experiment where advanced juveniles were stocked and lower rate of survival was recorded where early juveniles were stocked. The average growth rate recorded from the rearing experiments was higher than the average growth rate of Penaeus indicus recorded from the adjoining Chilka lake which indicates the promising future of prawn farming in and around the Chilka lake. Analysis of gut contents revealed that Penaeus indicus could efficiently utilise the algal and higher plant matter present in the ponds. No noticeable differences in daily growth rates were noticed between early and advanced juveniles in the rearing experiments